Crop Sorghum Ensiled With Unsalable Vegetables Increases Silage Microbial Diversity - Forwood, Daniel L.; Hooker, Kristian; Caro, Eleonora; Huo, Yuxin; Holman, Devin B.; Meale, Sarah J.; Chaves, Alex V. (Frontiers in Microbiology, 2019)
Ensiling vegetables with forage crops is a suggested method of waste diversion and can be directly utilized as a livestock feed. Carrot or pumpkin, ensiled at 0, 20, or 40% dry matter (DM) with crop sorghum, and with or without a second-generation silage inoculant were assessed for nutritive composition, organic acid profiles, aerobic stability and in vitro rumen fermentation characteristics. The study was a completely randomized design, with the fixed effects consisting of vegetable type (carrot vs. pumpkin), level (i.e., the level of vegetables), inoculant (inoculant or non-inoculant) and the interactions, and mini-silos within treatment as the random effect. The experimental unit for sorghum treatments represented by each mini-silo (5 kg capacity). Silage was sampled after 70-days ensiling for nutrient composition, 14-day aerobic stability, organic acid profiles and microbial diversity. After 24 h in vitro incubation, rumen fermentation parameters were assessed, measuring gas and methane (CH4) production, in vitro digestibility and volatile fatty acid concentrations. Sorghum ensiled with carrot or pumpkin at 20% or 40% DM increased crude fat (P ≤ 0.01) and decreased (P ≤ 0.01) silage surface temperature upon aerobic exposure compared to the control. Bacterial communities analyzed through 16S rRNA gene sequencing linearly increased (P ≤ 0.01) in diversity across both vegetables when the vegetable proportion was increased in the silage; dominated by Lactobacillus species. ITS analysis of the fungal microbiota upon silage opening and after 14 days (aerobic stability) identified increased (P ≤ 0.03) fungal diversity with increasing vegetable proportions, predominantly populated by Fusarium denticulatum, Issatchenkia orientalis, Kazachstania humilis, and Monascus purpureus. Upon assessment in vitro, there was an increase (P ≤ 0.04) in in vitro digestibility and some CH4 parameters (% CH4, and mg CH4/g DM), with no effect (P ≥ 0.17) on remaining CH4 parameters (mL CH4/g DM, mg CH4/g digested DM), gas production or pH. However, increasing vegetable amount decreased percentage of acetic acid and increased percentage of propionic acid of the total VFA, decreasing A:P ratio and total VFA concentration as a result (P ≤ 0.01). The results from this study indicate including carrot or pumpkin at 20 or 40% DM in a sorghum silage can produce a highly digestible, microbially diverse and energy-rich livestock feed.